Les défis posés par l’unité pédagogique pour élèves allophones arrivants (UPE2A) à la forme scolaire - Isabelle Rigoni (Recherches en Éducation)
Pupils categorized by the educational institution as newly arrived allophone pupils have, under the consideration of special educational needs, compensatory rights materialized by linguistic and pedagogical support in a pedagogical unit for incoming allophone pupil or in other specific systems. Under the paradigm of the inclusion of all students, they are enrolled in a regular class and operate back and forth between their class and the device. This situation creates challenges for the school form and structures in a unique way the teaching and learning relationships as well as the social relationships between pupils. We propose a reading of the adaptations of the pedagogical relationship based on the space-time relationship.